Near fault earthquakes and behaviour of liquid storage tanks - Sreekala, R.; Prasad, A. Meher; Muthumani, K.; Lakshmanan, N.; Iyer, Nagesh R. (Journal of Structural Engineering, 2024)
Near fault earthquakes are common in recent years and are known for the unique strong ground motion characteristics. Dynamic behavior of liquid storage tanks during strong ground motion requires lot of research attention and sloshing is one of the major concerns in the design of liquid storage tanks. Simulated experimental investigations using 3D shake tables are rare in this field and the nonlinear dynamic behavior of the structure is of interest, especially during near fault earthquakes. The paper presents an experimental investigation under simulated conditions on a fixed base rectangular container with water. The tank has been designed to suit experimental requirements and the dimensions were selected to fit the structure in 2m- tri axial shaking table. The behavior of the system is identified during dynamic loading using harmonic excitation and simulated earthquake studies were carried out further on the 3D shaking table. Higher dynamic pressures on the walls and increased dynamic loads on the tank due to the pulse characteristics of ground motion have been verified during the investigation. Computational modeling has been carried out on the experiments conducted and the results are discussed. Dynamic free surface flow is simulated using moving mesh interface and the fluid motion is modeled with incompressible Navier-Stokes formulation.